Virginia Hoel, Faith, Fatherland and the Norwegian Seaman: The work of the Norwegian Seamen’s Mission in Antwerp and Dutch Ports 1864-1920 - Feys, Torsten (BMGN - Low Countries Historical Review, 2017)
Virginia Hoel, Faith, Fatherland and the Norwegian Seaman: The work of the Norwegian Seamen’s Mission in Antwerp and Dutch Ports 1864-1920 (Hilversum: Verloren, 2016, 476 pp., isbn 978 90 8704 564 7).